The construction of illegality: Basotho migrant domestic workers' experiences - Makoro, Mantuna (My University, 2016)
The following research is a study on migrant Basotho Domestic workers. This research details their reasons for migrating by looking at socio economic and cultural factors that are at play in Lesotho. It documents their journey to South Africa by studying the border and how it constructs their illegality. This paper argues that by labelling migrants as illegal, South Africa is in fact perpetuating Basotho’s vulnerability and exploitation by South African employers. It also shows that there is a contradiction between South African labour, ILO convention 189 and Immigration act as the two former laws aim to protect migrants which the Immigration Act does not favour migrant domestic workers.
This research report is in fulfilment of the requirements for the award of a degree of Masters in Anthropology Ethics protocol number H14/08/40 Department of Anthropology- Faculty of humanities University of the Witwatersrand March 2015